Ethics and Responsibility in Political Demagogy: A Conceptual Review and Practical Implications - Cici Kumalasari; Muhammad David; Panggih Nur Adi; Siti Zahara Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research examines ethics and responsibility in the practice of political demagogy with the aim of understanding the conceptual and practical impact of this phenomenon. Political demagogy is defined as a practice in which leaders use manipulative rhetoric to influence the masses in favour of specific political interests. This research found that demagogy is characterised by emotional manipulation, distortion of facts, and populist rhetoric that exacerbates the polarisation of society. From an ethical perspective, demagogy violates the principles of honesty and transparency and exploits public fear and discontent, which can undermine trust in democratic institutions and increase social instability. The responsibility of political leaders is crucial in this context. Leaders are expected to maintain integrity, put the public interest first, and encourage constructive dialogue, as well as protect democratic institutions from the damage caused by demagogy. The research also identifies several practical steps needed, including improved political education and media literacy, as well as strengthened regulation against disinformation. Overall, this research emphasises the importance of a deep understanding of ethics and responsibility in politics to prevent the misuse of demagogy and ensure the health of democracy. With a comprehensive approach, society can be protected from the negative impacts of demagogy, and democracy can be better sustained.